BS EN 61000-3-3 AMD2. Electromagnetic compatibility (EMC). Part 3-3. Limits. Limitation of voltage changes, voltage fluctuations and flicker in public low-voltage supply systems, for equipment with rated current ≤16 A per phase and not subject to conditional connection (15th May 2020) - British Standards Institution,
No abstract available